PERAN GENDER DALAM PENGAMBILAN KEPUTUSAN PADA ERA REFORMASI DI INSTITUSI KEPOLISIAN - Setyawati, Novita Wahyu; Ningrum, Endah Prawesti (JURNAL ILMIAH M-PROGRESS, 2018)
The Police are in the process of reforming the gender, namely the change of a police organization into a professional and responsible police force and implement a policing style that is responsive to the needs of the local community. Where in the act of finding solutions and decision-making field did not see any differences between men and women. The purpose of this study is to examine the role of gender in decision making in the reform era in Police institution (South Bekasi Police Station case study). Analytical methods used are qualitative, through the stages of data interpretation, data reduction, data preparation, examination of data validity, and draw conclusions. The new view that women have equal rights and opportunities and their potential will expand the space for women and the presence of female figures in the public dimension, to be treated proportionally and not to rule out their opinions and make decisions. Keywords: Gender Roles and Decision Making.